Determine the vertical ground reaction forces and knee mechanics with different gait inclinations in the sheep model. Issue 4 (2nd August 2022) - Spatholt, Rebecca J.; Minoughan, Chelsea E.; Gooch, Cynthia; Harms, Samuel P.; Taylor, Michal L.; Galloway, Marc T.; Shearn, Jason T.
Abstract: Our current understanding of knee mechanics and anterior cruciate ligament (ACL) function is predominately based on data recorded during simulations of clinical examinations or the application of nonphysiologic loads and motions. These methodologies provide little information on knee and ACL mechanics during activities of daily living (ADLs). Additionally, researchers have not directly measured knee kinetics, knee contact pressures, and ACL forces, and it is unknown how these parameters change with different activities. This study quantified the effects of activity level on vertical ground reaction forces, knee kinematics, and joint and ligament forces during in vivo motions. Five female Suffolk sheep were walked twice weekly on a treadmill during level (0°), inclined (+6°), and declined (−6°) gait for 12 weeks. Electromagnetic (EM) trackers were surgically implanted onto the left distal femur and the left proximal tibia, and in vivo motions were recorded for all activities. Following sacrifice, the in vivo motions were applied to their respective knees using a serial robot with a multi‐axis load cell. In vitro simulations were repeated to measure (a) total knee forces, (b) contact pressure maps, and (c) ACL‐only forces. Declining the gait surface led to increased posterior translation during the swing phase and decreased flexion at hoof‐strike, decreased medial contact pressure at push‐off, decreased ACL force at hoof‐strike and increased ACL force at push‐off. This study established a system that can be used to examine knee mechanics and ACL forces during ADLs for different knee states to define design requirements for ACL reconstruction techniques.